A37 DEFECTS IN INTESTINAL MUCUS DISRUPTS THE REPERTOIRE OF DEVELOPING T CELLS IN THE THYMUS. (15th March 2019) - Tsai, K; Huang, Y; Ma, C; Vallance, B; Priatel, J
Abstract: Background: Severe, chronic inflammation of the intestinal tract is a defining hallmark of inflammatory bowel diseases (IBD) such as ulcerative colitis (UC) and Crohn's disease. IBD is postulated to result from a complex combination of environmental and genetic factors that lead to excessive bacterial stimulation of the mucosal immune system. An overlying layer of mucus functions to segregate contents of the intestinal lumen from the intestinal epithelium and the underlying immune system. Importantly, decreased mucus production and impaired mucus function have been associated with UC pathogenesis. MUC2 is the primary intestinal mucin and acts as a structural scaffold for mucus formation - forming a physical barrier to shield the intestinal wall. However, recent work suggests that mucus may also function to maintain immunological tolerance towards luminal antigens by promoting the regulatory activity of intestinal antigen-presenting cells. Currently, it is unclear what role mucus plays in influencing the T cell repertoire and modulating T cell immunity both at local and distal sites. We hypothesize that mucus is essential for maintaining T cell tolerance towards intestinal luminal antigens and preventing disease caused by constitutive T cell activation. Aims: To investigate whether peripheral T cells become highly activated in young, mildly colitic Muc2 -/ - mice following oral antigen gavage. Methods: To test our hypothesis, young (6–10 week old) wild type and MUC2-deficient ( Muc2 -/ - ) mice were gavaged with the model antigen ovalbumin (OVA) and the elicited OVA-specific T cell responses monitored at various time points post-treatment. Results: We found that oral administration of OVA resulted in the antigen rapidly escaping the gut and disseminating throughout the blood and lymphoid tissues of Muc2 -/ - but not wild type mice. Given the systemic spread of antigen in the Muc2 -/ - mice, we next sought to investigate whether the selection of developing T cells in the thymus of Muc2 -/ - mice was impacted by dietary antigens. Remarkably, we found that gavage of Muc2 -/ - mice led to presentation of OVA by thymic dendritic cells and the deletion of OVA-specific thymocytes whereas T cell development in wild type mice appeared unaffected. Conclusions: Based on our results, we concluded that oral antigens are rapidly disseminated throughout Muc2 -/ - mice. The heightened concentration of oral antigens induced rapid depletion of oral antigen-specific double positive (DP) thymocytes, and altered the T cell repertoire. Future studies will explore whether IBD patients suffering from impaired gut mucus structure/function also suffer defects in their T cell repertoires. Funding Agencies: CIHR